TS SPECIMEN LIFE PREDICTION OF HIGH-STRENGTH STEEL RESISTANCE SPOT WELDS - ZHANG Yu; LI DaYong; TANG WeiQin (Jixie qiangdu)
The plastic zone in crack tip influences life prediction result when using crack propagation method to predict fatigue life of spot welds. Most of the methods used to predict fatigue life don’t take plasticity into consideration. In this paper,TS specimen fatigue life of several high strength steels are tested and crack propagation method is used to predict theoretical fatigue life of TS specimen. Plasticity in crack tip is taken into consideration to modify the life prediction result. Predicted life in high cycle fatigue area barely change while life in low cycle fatigue area decrease after plastic modification. The modified life prediction result is in good agreement with experiment data. In high cycle fatigue area,plastic zone radium is small and has little influence on fatigue life because of low load. In low cycle fatigue area,plastic zone radium is big and influence life prediction result because of high load.